Analisis Perbedaan Tingkat Kebangkrutan Menggunakan Metode Altman Z-Score dan S-Score Springate pada Perusahaan Pariwisata Sebelum dan Selama Pandemi Covid-19 - Hanifah Mansyurah; Mayar Afriyenti (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the difference in bankruptcy rates in tourism companies before and during the Covid-19 pandemic.The results showed that there were different results in predicting bankruptcy before and after the pandemic. The results of this study indicate the potential for financial distress using Altman's Z